From Agasa Cristie to Group Image Play-Analysis of Horror Survival Game Panic Room : Escaping from the Den on Emotional Elements Development - Doo Heon Song; Hae Kyung Rhee; Ji-eun Kim; Jong Hee Lee (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A maniac computer game genre called "Survival Horror Games‟ is aimed for making gamers feel cathartic feeling when they escaped from the designed horror successfully. The degree of gaming quality, however, is not easy to measure. In this paper, we apply Caillois‟ game playing categories and other standards to measure how a game induces the feeling of fear and other emotional experience to players. Once dominated horror survival game series called Panic Room: Escaping from the Den was chosen to analyze and evaluate with those standards as well as its narratives and subsystems. Especially the 2nd version was most welcomed to users among 4 versions thus we focused on the difference between the version 1 and the version 2 in terms of game playing and fear elements in the game content and story structure. In result, version 2 showed much more Agon and Mimicry and all other fear elements than version 1. The group image playing structure and conference/collection subsystem that were newly provided to version 2 were attributed to its success.